2019
DOI: 10.3390/v11090768
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Novel RNA Viruses in Aquatic North American Wild Birds

Abstract: Wild birds are recognized viral reservoirs but our understanding about avian viral diversity is limited. We describe here three novel RNA viruses that we identified in oropharyngeal/cloacal swabs collected from wild birds. The complete genome of a novel gull metapneumovirus (GuMPV B29) was determined. Phylogenetic analyses indicated that this virus could represent a novel avian metapneumovirus (AMPV) sub-group, intermediate between AMPV-C and the subgroup of the other AMPVs. This virus was detected in an Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 69 publications
2
51
0
1
Order By: Relevance
“… 2018, 2019, 2020 ; Canuti et al . 2019 ) and these cluster with the sequences from wild birds, forming a clade that is distinct from AvCoV (Fig. 1 ).…”
Section: The Wild Bird Clade Of Avcov Now Constitutes a Novel Speciesmentioning
confidence: 98%
See 1 more Smart Citation
“… 2018, 2019, 2020 ; Canuti et al . 2019 ) and these cluster with the sequences from wild birds, forming a clade that is distinct from AvCoV (Fig. 1 ).…”
Section: The Wild Bird Clade Of Avcov Now Constitutes a Novel Speciesmentioning
confidence: 98%
“… 2018 , 2019 , 2020 ; Canuti et al . 2019 ). This is creating a new narrative in which disease-causing viruses are the exception rather the rule.…”
Section: Coronaviruses Causing Disease In Wild Birdsmentioning
confidence: 99%
“…Canuti et al. (2019) reported that a novel GuCoV (B29) was identified in great black‐backed gulls ( L. marinus ) (3/26, 11.5%) and American herring gulls ( Larus argentatus smithsonianus ) (2/24, 8.3%) belonging to the Charadriiformes order. GuCoV B29’s phylogenetic analysis indicated that this virus may represent a novel species within the gamma‐CoV family, similar to other novel CoV species described recently (Canuti et al., 2019).…”
Section: Global Distribution Of Coronavirusesmentioning
confidence: 99%
“…Wild birds are known viral reservoirs, and birds which live mainly in the marine environment are also known to harbor coronaviruses. For instance, a novel coronavirus within the Gammacoronaviruses was identified in American herring and great black backed gulls (Canuti et al, 2019). Interestingly, these sea bird coronaviruses are within the same clade as marine mammal coronaviruses (Figure 1), suggesting that in the past, transmission between these animals has occurred.…”
Section: Marine Coronavirus Diversitymentioning
confidence: 99%